1979
DOI: 10.1007/bf00523668
|View full text |Cite
|
Sign up to set email alerts
|

A bioceramic endoprosthesis for the replacement of the proximal humerus

Abstract: In patients with malignant tumors in the region of the shoulder, radical resection can avoid amputation in most instances. To improve the function of the arm, endoprosthetic replacement of the defect is desirable. A three-component endoprosthesis made of a bioceramic material (aluminium oxide) was designed, implanted without bone cement. Fast anchorage to bone is achieved by using a conical sleeve, fixed upon the previously conically reamed humerus shaft. A stable primary fit is always feasible. Subsequent bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 12 publications
0
6
0
3
Order By: Relevance
“…In these cases, soft-tissue reattachment is especially important to prevent future dislocations. 7,20,[48][49][50] Other materials and techniques are currently being investigated to improve soft-tissue integration. 16,[25][26][27][28]36,[38][39][40]67 In the proximal tibia, the gastrocnemius fl ap can be reinforced using various materials such as artifi cial acrylic meshes (eg, Lars, Trevira) or other biologically derived devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, soft-tissue reattachment is especially important to prevent future dislocations. 7,20,[48][49][50] Other materials and techniques are currently being investigated to improve soft-tissue integration. 16,[25][26][27][28]36,[38][39][40]67 In the proximal tibia, the gastrocnemius fl ap can be reinforced using various materials such as artifi cial acrylic meshes (eg, Lars, Trevira) or other biologically derived devices.…”
Section: Discussionmentioning
confidence: 99%
“…6 In these early reports, signifi cant diversity existed among the various devices utilized. In 1973, Parrish 5 reported his experience using homologous cadaveric allografts to reconstruct joint defects created by tumor excision, and in 1979, Salzer et al 7 described the use of a modular ceramic endoprosthesis for the replacement of the resected proximal humerus. In 1980, Katznelson and Nerubay 8 performed a total femoral reconstruction in 5 patients using a device that extended from the hip to insert directly into the proximal tibia without an articulating knee joint.…”
Section: Introductionmentioning
confidence: 99%
“…It is our opinion that in this situation, where reduction is not performed, the dislocated endoprosthesis then acts like an unconstrained endoprosthesis. 6,[17][18][19] With the new constrained liner the risk of dislocation seems to have been eradicated, and hence functional results will improve further. The four cases in which the new constrained liner was used showed no dislocations and improved functional results.…”
Section: Discussionmentioning
confidence: 99%
“…4 Since then, some authors reported some cases, and in the 1960s case series also appeared, but the indications for arthroplasty in early reports were dislocation fractures and rheumatoid arthritis. Applications of a massive endoprosthetic replacement, not only for the humeral head but also from proximal diaphysis to humeral head after resection of bone tumors, were reported by Salzer 24 in 1979 and Campanacci 5 in 1982. Although about 30 years have passed since the first report on endoprosthetic reconstruction, instability of the shoulder joint after it is still an unsolved problem.…”
Section: Discussionmentioning
confidence: 95%